1985
DOI: 10.1210/jcem-60-2-290
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Free Fatty Acids on Growth Hormone(GH)-Releasing Hormone-Mediated GH Secretion in Man*

Abstract: The effect of FFA on GH-releasing hormone (GHRH)-mediated secretion of GH was examined in six normal young men. Three of the men were infused with 250 ml of a lipid-heparin solution at 1.67 ml/min for 150 min, and the other three were given an equivalent volume of saline in the same manner. Thirty minutes after the start of infusion, 100 micrograms GHRH (the 44-amino acid form) were injected iv, and plasma GH and FFA were measured. One week later, the same men participated in an identical experiment, but the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(64 citation statements)
references
References 19 publications
5
57
0
2
Order By: Relevance
“…18 A similar GH suppression by FFA was reported in rats. 19 Our data also show FFA plasma levels in obese pre-BPD subjects, signi®cantly higher than in normal weight ones.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…18 A similar GH suppression by FFA was reported in rats. 19 Our data also show FFA plasma levels in obese pre-BPD subjects, signi®cantly higher than in normal weight ones.…”
Section: Discussionsupporting
confidence: 69%
“…22 Among peripheral factors, metabolic fuels could directly in¯uence the hypothalamic balance between stimulating and inhibition factors for GH. GH is not suppressed by oral glucose in obesity, 18 but the further increase after a meal could indicate not only a lack of inhibition, but rather an altered hypothalamic sensitivity to metabolites. Maccario et al 23 observed that while pirenzepine, a direct cholinergic drug, abolished the GH response to GHRH and arginine, as in normal humans, obese subjects differed from the controls with respect to glucose action; the GHRH-and arginineinduced GH release were refractory to the inhibitory effect of glucose.…”
Section: Discussionmentioning
confidence: 98%
“…FFA elevations reduce or block GH secretion stimulated by a variety of stimuli or conditions, such as FFA depression, hypoglycemia, physical exercise or administration of GH releasing hormone (GHRH) or GHRP-6. 3,4 There is now compelling evidence indicating that the FFA blockade of GH secretion is exerted at the pituitary level, probably by direct inhibition of somatotroph function. 4,5 The effect of FFA on GH secretion is exerted at physiological levels, since reduction in circulating FFA levels following administration of acipimox, per se stimulates basal GH secretion as well as increasing GH responses to different GH secretagogues in normal subjects.…”
Section: Free Fatty Acids and Gh Secretionmentioning
confidence: 99%
“…The increased plasma FFA suppressed GRF-induced GH secretion in rats [27]. The plasma FFA increase induced by an intravenous infusion of lipid-heparin inhibited GH secretion in response to GRF in man [28]. In sheep, the intravenous infusion of FFA has also been reported to suppress the frequency of GH pulses and the GH response to GRF [29].…”
Section: Discussionmentioning
confidence: 99%